Texture Segmation Based Filters for Water Images - Umamaheswari, M (International Journal of Computer Sciences and Engineering, 2025)
Image segmentation is a mechanism used to divide an image into various segments. It will make image flat and easy to evaluate. Segmentation process also helps to find region of interest in a particular image. The main goal is to make image simpler and meaningful. Image Segmentation is an main pixel based measurement of image processing which often has a large impact on quantitative image study result. The texture is the main attribute in many image analysis or computer vision applications. The procedures developed for texture segmentation can be subdivided into four categories: structural approach, statistical approach, model based approach and filter based approach. Different definitions of texture are described, but more importance is given to filter based methods, such as Median Filter, Gaussian Smoothing and Mean Filter. These filters are used in Water images. The main objective of this analysis is to study different filtering methods for texture segmentation of water images